An unusual case of osteoarthritis? - Mariana Teixeira; Joana Ricardo Pires; Filipa Coroado Ferreira; Tiago Rabadão; Marcelo Aveiro; Nuno Neves; Clarinda Neves (Clinical Case Reports, 2021)
Abstract Forestier disease is a condition characterized by calcification and ossification of ligaments and entheses particularly affecting axial skeleton. Diagnosis is difficult and mandates a high suspicion level, but unexpensive and accessible examinations like a simple radiography might provide useful diagnostic clues in these challenging clinical scenarios and improve clinical assistance.